Contribuições do PIBID para a formação inicial de futuros professores de biologia – o caso do Instituto Federal do Piauí (IFPI) - Barros, Yara Silvya Albuquerque Pires (2018)
This academic word discusses the contributions of the Institutional Program of Initiatives for Teaching (PIBID) in the process of initial training of Biology teachers, taking into as a study universe the Central Campus, in Teresina, of the Federal Institute of Education, Science and Technology of Piauí (IFPI). Considering that the institutes, although possessing the specificity of the offer for professional and technological education, they present themselves as another locus of teacher training for the basic school; that the PIBID aims to contribute to strengthening and improving the quality of academic activities developed in undergraduate courses, and that the articulation between theory, practice and interdisciplinarity are the program pedagogical foundations. The objectives of this study were: analyzing the perceptions of scholarship students, area coordinators and supervisors who develop the initial formation process within PIBID, focusing on the implications of articulation theory and practice and interdisciplinarity in the formative process for teaching. To this end, it pursues the following specific objectives: i. identify, in the actions and activities developed within the scope of the Program, the strategies and procedures used to promote the articulation between theory and practice; ii. in the same way, to identify the strategies and procedures used to promote interdisciplinarity. The study has a qualitative nature and used the following methodological steps: bibliographic research, which raised and analyzed published academic texts (articles, dissertations, theses and books), to provide theoretical and methodological support to research and to make known the state of the art of production academic research on PIBID and teacher training; a documentary survey that analyzed the educational legislation that guides teacher education and public policies in this area, the legal documents that regulate the PIBID in the federal context and, at the level of the IFPI, the institutional project and the annual reports of activities. To collect data, we used systematic (non-participant) observation of the activities carried out by the students at schools and reported in the field diary and the semi-structured interview. For the analysis of the data, the technique of Discourse Analysis is used, taking into account Orlandi's methodological recommendations, and taking articulation, theory and practice and interdisciplinarity as the main categories of the study. The research carried out leads us to conclude that in the activities and projects of PIBID - subproject of Biology, the articulation theory and practice are based on the practical application of theory, and interdisciplinarity, on the juxtaposition of disciplines and contents, facing difficulties for its effectiveness in the scope of this subproject, are aspects that are added to the theoretical-practical formation realized in the context of the graduation to base and to improve the pedagogical work in this process of being a teacher.